EGFR signaling is required for the differentiation and maintenance of neural progenitors along the dorsal midline of the Drosophila embryonic head. - Dumstrei, K.; Nassif, C.; Abboud, G.; Aryai, A.; Aryai, A.; Hartenstein, V. (Development, 1998)
EGFR signaling has been shown in recent years to be involved in the determination, differentiation and maintenance of neural and epidermal cells of the ventral midline (mesectoderm and ventromedial ectoderm). Localized activation of the TGFalpha homolog Spitz (Spi) in the mesectoderm is achieved by the products of the genes rhomboid and Star. Spi binds to its receptor, the Drosophila epidermal growth factor receptor homolog (Egfr), and triggers the Ras pathway which is needed for the survival and differentiation of ventral midline cells. The results reported here indicate that EGFR signaling is also required in a narrow medial domain of the head ectoderm (called 'head midline' in the following) that includes the anlagen of the medial brain, the visual system (optic lobe, larval eye) and the stomatogastric nervous system (SNS). We document that genes involved in EGFR signaling are expressed in the head midline. Loss of EGFR signaling results in an almost total absence of optic lobe and larval eye, as well as severe reduction of SNS and medial brain. The cellular mechanism by which this phenotype arises is a failure of neurectodermal cells to differentiate combined with apoptotic cell death. Overactivity of EGFR signaling, as achieved by heat-shock-driven activation of a wild-type rhomboid (rho) construct, or by loss of function of argos (aos) or yan, results in an hyperplasia and deformity of the head midline structures. We show that, beside their requirement for EGFR signaling, head and ventral midline structures share several morphogenetic and molecular properties.